Pengaruh Harga, Promosi Penjualan, dan Citra Merek Terhadap Keputusan Pembelian Pada Produk H&M - Antonius Kristian; Jonathan Widarta Wijaya; Steven Virgus Yudistira; Patrick Heaven (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to evaluate the influence of price, sales promotion, and brand image on the purchasing decision of H&M products. The research uses a quantitative approach with a survey method, where questionnaires were distributed to consumers who had purchased H&M products in Västerås. The analysis includes descriptive analysis, classical assumption tests, multiple linear regression, and hypothesis testing. The results show that price, sales promotion, and brand image significantly affect the purchasing decision of H&M products. Setting the right price can strengthen consumers' positive perception of product quality and increase purchasing decisions. Effective sales promotions can attract consumer attention and expand market share, while a strong brand image is important for building consumer loyalty and trust. The F-test indicates that these three variables jointly have a significant effect on purchasing decisions. Meanwhile, the t-test reveals that price, sales promotion, and brand image individually have a positive impact on purchasing decisions. Based on these findings, it is expected that the company can focus more on competitive pricing strategies, attractive promotions, and strengthening brand image to improve purchasing decisions for H&M products.